Winnicott’s Theories on the Influence of an Infant’s Early Environment on the Development of Anti-social Tendencies in Adolescence - Pretorius, Nicky (Auckland University of Technology, 2014)
This dissertation explores the links between the infant’s early environmental experience and the development of anti-social tendencies in adolescence. Using an interpretive literature review of the work of Donald Winnicott, a psychoanalyst and paediatrician, this study considers his theories on both the early infant experience and juvenile delinquency and establishes a relationship between them. It also explores the relevance of Winnicott’s theories to contemporary practice in Aotearoa New Zealand. The research findings demonstrate a clear correlation between failures of the environmental provision at a stage of relative dependence and the onset of anti-social tendencies in adolescence. The study also suggests Winnicott’s theories are relevant within contemporary psychoanalytically informed psychotherapeutic practice in Aotearoa New Zealand. The study offers suggestions for further research in particular with regards to Winnicott’s contributions to practice within Maori models of health.
Keywords: Psychotherapy; Winnicott; Literature review; Juvenile delinquency; Maternal environment